Light-induced nitric oxide release from physiologically stable porous coordination polymers1. Issue 34 (14th September 2015) - Kim, Chiwon; Diring, Stéphane; Furukawa, Shuhei; Kitagawa, Susumu
<x xml:space="preserve">Abstract</x> A physiologically stable PCP based on titanium ions produces nitric oxide from bis-N-nitroso functionality on ligands under light irradiation.